IMPLEMENTATION OF BUSINESS ETHICS IN INCREASING CONSUMER PURCHASE INTEREST AND SATISFACTION - Abu Bakar Akbar (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this research is to find out how the application of Islamic Business Ethics to Drinks at Teh Tarik Jodi Manahan increases buying interest and consumer satisfaction. This research method is qualitative research with a descriptive approach. Data collection was carried out through observation techniques, in-depth interviews and documentation. Data analysis was carried out qualitatively using procedures, namely through the process of data collection, data sources, data analysis and data validity. From the results of this research, it can be seen that in the application of Islamic business ethics, it has been fully implemented, including the principles of orderly administration and transparency in price setting, which has been implemented is relying on God's provisions (tauhid), selling halal and good quality goods, not using oaths, being loose and be generous. The impact of implementing Islamic business ethics is that life becomes more blessed and fulfilled and the number of customers increases so that income also increases. Obstacles faced include unstable raw material prices, the solution is that traders must be clever at innovating and creative so that profits can be maximized, tight business competition, the solution is to highlight food and drinks that are their specialty, traders cannot predict market conditions, the solution is to cook less food if it is finished cooking again. The final obstacle is that the quality of taste can change at any time. The solution is that the stall owner must ensure the quality of the taste of the food and drinks he sells himself.